Limnophora riparia - Michelsen, Verner (Zenodo, 2021)
Limnophora riparia (Fallén) (Figs 10D‒F, 12D, 13B) Calliophrys riparia (Fallén); Becker 1908a: 105 (Tenerife); Becker 1908b: 195 (Madeira); Frey 1936: 132 (Tenerife). Limnophora (Calliophrys) riparia capoverdica Emden; Emden 1958: 11 (Cape Verde Is.). Syn. nov. Limnophora (Melanochelia) riparia (Fallén); Santos Abréu 1976: 101 (La Palma). Limnophora (Calliophrys) riparia (Fallén); Hennig 1960: 391, text fig. 70C, plate figs 189, 281; Báez 1981: 637, pl. 1 fig. 8 (Tenerife, La Palma). Limnophora riparia (Fallén); Pont 1980: 749. Material examined. CAPE VERDE ISLANDS [MZH]: São Nicolau: Chã da Preguisa, 1♂, 1♀ [holotype and paratype of L. riparia capoverdica Emden, 1958] 13‒17.xii.1953 (H. Lindberg]. CANARY ISLANDS [MZH, NHMD]: TENERIFE: Icod de las Vinos, 1♂ 1931 (R. Frey). LA GOMERA: La Laja, 28°06´N 17°11´W, 480‒ 600m, 1♀ 22‒29.i.2016 (V. Michelsen). Further European material in NHMD seen from Denmark, Greece (Crete), Iceland, Spain and Sweden. Taxonomic note. Emden (1958) proposed the subspecies Limnophora (Calliophrys) riparia capoverdica for the Cape Verde population of the widespread Palearctic L. riparia , based on some differences in colour of the head and mesonotum and length of the aristal branches. On direct comparison of type specimens (see above) with specimens from the Canary Islands and various European countries I found that the colour falls within the variation of the nominal species and that the difference pertaining to the arista is non-existing. Therefore, Limnophora (Calliophrys) riparia capoverdica Emden is here considered as a synonym of Limnophora riparia (Fallén), syn. nov. Diagnosis. Small to medium sized, wing length 3.8‒5.5mm. Male: Arista short-pubescent, longest branches not quite as long greatest width of arista. Frons broad, flat, near horizontal, widening towards lunule; vertex and fronto-orbital plates in dorsal view greyish brown pruinose, long frontal triangle silvery white pruinose, frontal vitta matt black. Parafacial plates silvery white with a black patch on vibrissal area. ...